Combined surgical procedures using laparoendoscopic single‐site surgery approach. Issue 3 (7th March 2013) - Palanivelu, C; Ahluwalia, Jasmeet Singh; Palanivelu, Praveenraj; Palanisamy, Senthilnathan; Vij, Anirudh
Abstract Introduction As our experience with laparoendoscopic single‐site (LESS) surgeries increased, we considered how it might be employed if two or more surgeries were to be combined. LESS surgeries' cosmetic advantages, decreased parietal trauma and better patient satisfaction relative to standard multiport laparoscopy have been previously reported, but its special role in combined surgeries has never been stressed. In this series, we present the advantages of LESS procedure over multiport laparoscopy in combined surgical procedures. To the best of our knowledge, this has never been reported before. Methods A retrospective analysis of 27 patients was performed. The patients underwent combined LESS procedures between February 2010 and January 2012 at GEM Hospital, Coimbatore, India. All patients were of ASA grade 1 or 2. Patients with previous surgery in the umbilical region were not offered single‐incision surgery. Results We successfully performed 27 combined LESS procedures over a span of 2 years. Twenty patients were women and seven were men. Mean age was 35.94 years (range, 10–66 years). Mean BMI was 27.2. There were no major intraoperative complications. Mean blood loss was 45.7 mL (range, 0.0–120.0 mL). Mean postoperative hospital stay was 3.08 days (range, 1–5 days). Conclusion When a suitable case of multiple pathologies is encountered and LESS surgery is feasible for all of them, performing LESS surgery not only has cosmetic advantages over standard laparoscopy, but it also avoids the need for additional ports to achieve adequate visualization and access. All quadrants of the abdomen remain under reach through umbilicus.